Optimization of approaches to the improvement of patients’ compliance to treatment of the hard severity degree of diabetes mellitus 2nd type by family therapy involvement - Tkachenko, Olga (ScienceRise: Medical Science, 2017)
Aim. To improve the quality of the treatment of patients with DM type 2 of hard severity degree at the expanse of the increase of medicamentous compliance to patients by family therapy involvement. Materials and methods. There were observed 174 patients with DM type 2 of hard severity degree, who underwent out-patient treatment. They were divided in groups depending on applied tactics of psychoprophylaxis of compliance disorders. Methods of research: clinical-anamnestic; clinical-psychopathologic; psychodiagnostic, statistical. Research results and their discussion. It was established that the one of node dyscompliance factors in patients with DM type 2 of hard severity degree is a disorder of cognitive functions that testify to the necessity of a side help involvement, including patients’ relatives into the control of medical prescriptions realization. The other dyscompliance factor of patients with DM type 2 to the therapy is an attitude of relatives to his/her disease. There were established two types of patients’ reaction to medical recommendations, appeared as a response of patient’s family members of his/her disease. All these reactions had dyscompliant character that conditioned a necessity of the correction work with patient’s relatives as a factor psychoprophylaxis of disorders of compliance to the therapy in patients with DM type 2. The elaborated system of prophylaxis of disorders of medicamentous compliance to the therapy in patients with DM type 2 of hard severity degree consisted of two links: indirect work with patients and work with patients’ family members with family therapy involvement. The high effectiveness of the elaborated the system of prophylaxis of disorders of medicamentous compliance to the therapy in patients with DM type 2 of hard severity degree was proved. In all patients, who underwent psychoprophylaxis by the elaborated system, the compliance level increased to maximal values. Conclusions. There were established the factors of dyscompliance to the medicamentous therapy in patients with DM type 2 of hard severity degree. The influence of family members’ reaction to patient’s disease on features of patient’s attitude to the therapy was determined. The system of prophylaxis of disorders of medicamentous compliance to the therapy in patients with DM type 2 of hard severity degree that included family therapy and direct work with patients’ relatives was elaborated. Its high effectiveness was noted